Monitoring and Enhancement of Mobile System Performance - Noori, Khalid S.; Fahad, Assmaa A. (Iraqi Journal of Science, 2020)
Android operating system, since its first start, is growing very fast and takes a large space in smart devices market. It is built and developed on Linux and designed basically for touch screen devices such as, mobiles, tablets, etc. Mobile devices are markedly complicated and feature-rich; therefore they are prone to reliability of software and performance problems. Because of the small resources, smart devices, such as CPU, RAM, suffer from problems. One of these problems is Software Aging (SA). SA is recognized in long running OSs as a shortage in resources, performance retreating, and finally failure. SA is looked at from two sides, namely the poor response time of application which represents the end user side and the shortage in metrics related to device resources, such as RAM and storage. In this paper, a set of eight experiments is conducted to distinguish SA in Android mobiles. These experiments are conducted to find the correlation between Launch Time (LT) with RAM and storage metrics covered in this paper. Statistical methods, such as Mann Kendall test, Sen’s slope, Spearman rank correlation, and Design of Experiment (DOE) are used to prove the correlation statistically. These experiments assist to detect SA, which will be helpful in the rejuvenation strategy of applications.